Various factors affecting the bacterial corneal ulcer healing: a 4-years study in referral tertiary eye hospital in Indonesia (Faculty of Medicine Universitas Indonesia, 2015)
Background: Corneal ulcer is one of the most common causes of visual acuity impairment and blindness all over the world. The aim of the study was to evaluate various factors affecting the bacterial corneal ulcers healing, including the predisposing factors, causative organisms, antibiotic sensitivity, as well as the treatment outcomes. Methods: All data were taken retrospectively from medical records of patients who underwent corneal scraping for Gram examination and/or culture over a-4-year period (2008-2011) at the Cipto Mangunkusumo Hospital Jakarta. Treatment outcome were analyzed using Chi-square test, one-way ANOVA, and post-hoc analysis. Mean time required for complete epithelial healing was also investigated. Results: 220 cases of bacterial corneal ulcers in 216 patients were included. The most common risk factors were ocular trauma (45.8%). Gram-positive coccus were found in 65.7% cases other than other microbes. Pseudomonas sp. (25,0%) and Staphylococcus epidermidis (18.4%) were the most common isolates, sensitive to almost all kinds of antibiotics. About 83.0% (106 cases) were improved with antibiotics only, the rest were not improved and worsened. Mean time for complete epithelial healing was 17.5 ± 8.9 days with mild ulcer had the most rapid recovery. Eyes treated with fluoroquinolone eyedrops were healed in 14 days, faster than other regiments. Conclusion: Ocular trauma was the most common risk factor for corneal ulcer, and the most commonly isolated organism was Pseudomonas sp. Most cases were improved with antibiotics, and fluoroquinolone showed faster healing. Complete epithelial healing occurred in about 17.5 days.